Incorporating Patients' Values and Preferences Into Decision Making About Transplantation of HCV-Naïve Recipients With Kidneys From HCV-Viremic Donors: A Feasibility Study. Issue 2 (November 2021) - Eckman, Mark H.; Adejare, Adeboye A.; Duncan, Heather; Woodle, E. Steve; Thakar, Charuhas V.; Alloway, Rita R.; Sherman, Kenneth E.
Introduction: While use of (hepatitis C virus) HCV-viremic kidneys may result in net benefit for the average end-stage kidney disease (ESKD) patient awaiting transplantation, patients may have different values for ESKD-related health states. Thus, the best decision for any individual may be different depending on the balance of these factors. Our objective was to explore the feasibility of sampling health utilities from hemodialysis patients in order to perform patient-specific decision analyses considering various transplantation strategies. Study Design: We assessed utilities on a convenience sample of hemodialysis patients for health states including hemodialysis, and transplantation with either an HCV-uninfected kidney or an HCV-viremic kidney. We performed patient-specific decision analyses using each patient's age, race, gender, dialysis vintage, and utilities. We used a Markov state transition model considering strategies of continuing hemodialysis, transplantation with an HCV-unexposed kidney, and transplantation with an HCV-viremic kidney and HCV treatment. We interviewed 63 ESKD patients from four dialysis centers (Dialysis Clinic Inc., DCI) in the Cincinnati metropolitan area. Results: Utilities for ESKD-related health states varied widely from patient to patient. Mean values were highest for -transplantation with an HCV-uninfected kidney (0.89, SD: 0.18), and were 0.825 (SD: 0.231) and 0.755 (SD: 0.282), respectively, for hemodialysis and transplantation with an HCV-viremic kidney. Patient-specific decision analyses indicated 37 (59%) of the 63 ESKD patients in the cohort would have a net gain in quality-adjusted life years from transplantation of an HCV-viremic kidney, while 26 would have a net loss. Conclusions: It is feasible to gather dialysis patients' health state utilities and perform personalized decision analyses. This approach could be used in the future to guide shared decision-making discussions about transplantation strategies for ESKD patients.